Violence and Desire in Brazilian Lesbian Relationships - Allen, Andrea Stevenson. author. aut Link
XII, 243 p.
Keywords: In Violence and Desire in Brazilian Lesbian Relationships, Allen examines the lives of Brazilian women in same-sex relationships. This examination contributes to interdisciplinary discussions of female same-sex sexuality, violence, race, and citizenship. Using fifteen months of ethnographic fieldwork, primarily with Afro-Brazilian women in the city of Salvador da Bahia, Allen argues that Brazilian lesbian women reject Brazilian cultural norms that encourage male domination and female submission through their engagement in romantic relationships with each other. At the same time Allen claims lesbian women also reproduce Brazilian cultural ideals that associate passion, intensity, and power with physical dominance through their engagement in infidelity and intimate partner violence. The book demonstrates that lesbian women are nonetheless marginalized as Brazilian citizens through widespread social and political invisibility despite these apparent displays of masculinized power.